Pengetahuan, Persepsi dan Sikap Perawat RSUD Arjawinangun tentang Asuhan Keperawatan Spiritual - Niko Sutrisno; Keksi Girindra Swasti; Wastu Adi Mulyono (Journal of Bionursing, 2019)
Background. Nursing considers humans as complex creatures which different one from another. They consist of biological, social, cultural, psychological and spiritual dimensions. However, the provision of spiritual care is not optimally delivered.Objective. This study was to describe nurses' knowledge, perceptions, and attitudes about spiritual careMethod. An observational study with cross sectional approach was conducted. Totally, 248 nurses worked in RSUD Arjawinangun Cirebon were invited to contribute in the study. The sample was collected by total sampling technique. Self-respon questioners were utilized, included knowledge, SSCRS and attitude scales. Univariate analyses were applied to describe the data.Results. Mosts of respondents indicated 10 years work experience. The education background varied from Diploma to Post-graduate, but the majority was Diploma 3 yrs. Female nurses dominated the sample with age ranged between 25 and 56 years old, but ages 26-35 dominatee the sample. Median scores of knowledge, perceptions and attitudes after being converted into 0-100 scale, all around 64.Conclusion. Scores of knowledge, perceptions and attitudes of Arjawinangun Hospital  nurses about spiritual care were in  mediocre levels.